In situ grown epitaxial heterojunction exhibits high-performance electrocatalytic water splitting - Zhu, Changrong (2019)
Electrocatalytic performance can be enhanced by engineering a purposely designed nanoheterojunction and fine‐tuning the interface electronic structure. Herein a new approach of developing atomic epitaxial in‐growth in Co‐Ni3N nanowires array is devised, where a nanoconfinement effect is reinforced at the interface. The Co‐Ni3N heterostructure array is formed by thermal annealing NiCo2O4 precursor nanowires under an optimized condition, during which the nanowire morphology is retained. The epitaxial in‐growth structure of Co‐Ni3N at nanometer scale facilitates the electron transfer between the two different domains at the epitaxial interface, leading to a significant enhancement in catalytic activities for both hydrogen and oxygen evolution reactions (10 and 16 times higher in the respective turn‐over frequency compared to Ni3N‐alone nanorods). The interface transfer effect is verified by electronic binding energy shift and density functional theory (DFT) calculations. This nanoconfinement effect occurring during in situ atomic epitaxial in‐growth of the two compatible materials shows an effective pathway toward high‐performance electrocatalysis and energy storages.